(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The rapid development of digitalization and the creation of electronic resources, in areas such as e-commerce, government portals and others leads to the actualization of data protection issues. The protection of electronic resources is becoming more and more relevant every day. This article presents the concept of adaptive protection of electronic resources from information security threats. In the course of this research, an adaptive model of protection of electronic resources from threats to information security based on behavioral analysis was developed.